Does Voiding Cystourethrogram Exclude Posterior Urethral Valves in Late Presenting Cases? - Özen, Mehmet Ali; Taşdemir, Mehmet; Gündoğdu, Gökhan; Bilge, Ilmay; Büyükünal, Cenk; Eroğlu, Egemen (European Journal of Pediatric Surgery, 2019)
Introduction Delayed presentation of posterior urethral valves (PUVs) is a rare condition. Presentation and diagnosis of the patients with late PUVs are challenging. Voiding cystourethrogram (VCUG) is mainly practiced. In this study, we aimed to evaluate the children with late-presented PUVs, and the reliability of VCUG in this group.Materials and Methods Between January 2003 and December 2017 records of patients who were diagnosed with late-presented PUVs were analyzed. Delayed presentation of PUV was defined as patients who were diagnosed and treated after infancy. Cases were examined in terms of age at diagnosis, presenting symptoms, urinalysis, urinary ultrasound, urodynamic studies, VCUG, and dimercaptosuccinic acid scintigraphy findings. Postoperative follow-up conditions were also assessed.Results Seventeen boys were diagnosed with late-presented PUVs (mean age was 7.35 years). The most common symptoms at presentation were frequency (58.8%), day and nighttime incontinence (47%), and febrile urinary infection (41%). PUV was noted by VCUG in 10 patients alone. The classical sign of dilated posterior urethra was detected in 9 patients. The 10th patient had posterior urethral irregularity. Urethra could not be evaluated due to unsuccessful voiding in one patient. Six patients had normally appearing urethra on VCUG. Reflux was detected in nine (52.9%) patients.Conclusion Late-presented PUVs may be missed on VCUG. Whether a PUV might be present is crucial in boys with a history of recurrent urinary infection, persistent reflux, and repetitive daytime incontinence. Based on our results, we conclude that cystoscopic examination should be preferred for those cases to diagnose PUVs regardless of VCUG results.
Keywords: late-presenting; posterior urethral valves; diagnosis; voiding cystourethrography; cystoscopy